Nagy Benedek esete Szenci Molnár Alberttel - Ajkay, Alinka (Studia Litteraria, 2026)
By the early 17th century, the Lutherans of Western Transdanubia had firmly established their separation from both Catholics and Calvinists. Among the region’s two great aristocratic families, the Batthyánys adhered to Calvinism, while the Nádasdys followed the Lutheran faith. Upon returning from his travels, Albert Szenci Molnár initially sought to integrate into this deeply divided religious landscape; one that, by the 1610s, was predominantly Lutheran. However, his efforts were hindered by the local Lutheran community, including Benedek Nagy of Sármellék, a schoolmaster in Kőszeg, who even composed a mocking pasquinade against him.